2019
DOI: 10.1590/1413-7054201943003819
|View full text |Cite
|
Sign up to set email alerts
|

Production of biocomposites from the reuse of coconut powder colonized by Shiitake mushroom

Abstract: The demand for biodegradable composite has grown worldwide in recent years, mainly in order to reduce environmental contamination by structural materials produced from the oil industry. The objective of this study was to evaluate the growth of isolates from the edible mushroom “Shiitake” (Lentinula edodes) in substrate coconut powder-based supplemented with wheat bran, as well as to analyze the influence of fungi growing period and drying time of the colonized substrate on the mechanical properties of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Such plant species should be selected to save the strain life. The most known substrates for the production of mycelium-based materials are wood chips [ 30 , 32 , 66 ], sawdust, straw [ 4 , 8 , 9 , 33 , 71 ], coconut powder [ 72 ], garden waste [ 14 ], and bagasse [ 4 ]. These substrates are selected due to their compatibility for fungal growth and their lignocellulosic content.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Such plant species should be selected to save the strain life. The most known substrates for the production of mycelium-based materials are wood chips [ 30 , 32 , 66 ], sawdust, straw [ 4 , 8 , 9 , 33 , 71 ], coconut powder [ 72 ], garden waste [ 14 ], and bagasse [ 4 ]. These substrates are selected due to their compatibility for fungal growth and their lignocellulosic content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, straw and bagasse have softer particle properties than sawdust, so the fungi can utilize nutrients easily from soft substrates than hard substrate according to [ 32 ]. To enhance the nutritional content, different supplements such as wheat bran [ 8 ]and rice bran and different agricultural straw [ 72 ] are mixed. Table 2 shows different mycelium-based materials with various strains, supplements, and substrates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So far, only one study reported the usage of shiitake as an effective mycelium-based material, using coconut powder with wheat bran as substrate, on the effect of fungi growth and mechanical properties (Matos et al 2019). Therefore, this work investigates the effect of solid-state fermentation from L. edodes on peach-palm sheath fibres using three different nutrient growing feed source treatments and evaluates the amount of enzymes produced.…”
Section: Introductionmentioning
confidence: 99%
“…At least 92 research papers have been published on mycelium-based composites (72 original articles [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ,…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%